Response to: Impact of luteal phase hysteroscopy and concurrent endometrial biopsy on subsequent IVF cycle outcome - Kumbak, Banu; Sahin, Levent; Ozkan, Sema; Atilgan, Remzi (Springer Heidelberg, 2015)
[Abstract Not Available]